Pengaruh Program Kajian Remaja Terhadap Akhlak Siswa Kepada Guru di SMP Negeri 2 Gemolong Tahun Ajaran 2015/2016 - Nidaul Mufidah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
The aims of the research are 1) to know the students attitudes who join teenager religious meeting program to the, 2) to know the students attitudes who do not join teenager religious meeting program to the teachers, 3) to know the influences of teenager religious meeting program to the students’ attitude to the teachers.The methods of this research are quantitative ex-post facto. The research is held at SMP Negeri 2 Gemolong Sragen in August 2015 up to January 2016. The population of this research is 190 students of the seventh and eighth grades. The sample is 148 students of the seventh and eighth grades. The data is analyzed by using normality test requirement by using chi quadrat formula, and hypothesis by using uji-t formula. We can conclude that 1) the students’ attitude who join religious meeting program for teenager to the teachers is at medium category which are 40 students, 2) the students’ attitude who do not join religious meeting program for teenager to the teachers is at medium category which are 108 students,3) the result of comparative analysis uji-t formula shows that the value of (thitung 11,588 > ttabel 1.960) which has significant level 5%, therefore there are influences of religious meeting program for teenager to the teachers.Keyword: religious meeting program for teenager, student's attitude to teachers